Hot-air drying shrinkage process of lignite and its cracking mechanism. (15th May 2022) - Gao, Mingqiang; Wan, Keji; Miao, Zhenyong; He, Qiongqiong; Xue, Shuwen; Dong, Xiuyong
Highlights: Volume shrinkage is caused by water removal. Within the selected range of experimental temperature, high-temperature drying leads to greater shrinkage owing to the fast water removal. The direction of surface crack development is consistent with the direction of moisture removal. In the range of 80–170 °C, high-temperature drying leads to greater moisture and shrinkage differences in lignite particles, resulting in more severe cracking. Abstract: Lignite fragmentation during drying can significantly impair the operation of a drying system. Volume shrinkage is the main factor that causes lignite fragmentation during low-temperature drying. A two-dimensional lignite plate was prepared for this study, and its drying behavior was analyzed. Instead of volume shrinkage, two-dimensional area shrinkage was measured because of the ease of measurement. The shrinkage characteristics of a two-dimensional lignite plate were studied using the shrinkage percentage, shrinkage rate, shrinkage kinetic model, and shrinkage activation energy ( Es ). The development of surface cracks was quantitatively analyzed. The results reveal that the sample shrinks continuously during drying and that the shrinkage is severe at a high temperature within the selected range of experimental temperature. The Weibull distribution function better predicts the shrinkage process of the two-dimensional lignite plate. Volume shrinkage is caused by water removal. High-temperature drying leads to greater shrinkage owing to the fast water removal. The high pressure of water vapor generated within the lignite plate can lead to the formation of a dense crack network on the surface during drying at a high temperature. The direction of surface cracking is consistent with the direction of moisture removal. The difference in moisture content between the outer layer and the core of lignite particles leads to a difference in their shrinkage. The outer layer produces tensile stress under restriction by the core, which leads to cracking. In the range of 80–170 °C, high-temperature drying results in greater moisture and shrinkage differences, resulting in more severe cracking.